Aliran Permukaan dan Erosi di Areal Tumpangsari Tanaman Pinus Merkusii Jungh. Et de Vriese - Rudi Ispriyanto; Nana Mulyana Arifjaya; Hendrayanto (Jurnal Manajemen Hutan Tropika, 2001)
The rate of surface run-off and erosion from the logged over pine forest plantation under tumpangsari system (taungya) management which combine the perrenial plant of one year old pine plantation and different annual crops on two different physical characteristic of catchment areas (Plot A and Plot B) were measured. Surface run-off from Plot A and B were 2 % and 0.3 % of rainfall respectively. The rate of erosion from Plot A and B were 6.7 and 0.9 ton/ha/yr respectively The rate of erosion from Plot A and B were higher than that of the previous pine forest plantation, but they were lower than the rate of tolerable erosion.